2019
DOI: 10.1542/peds.2018-3011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Related Emotional Distress Over Time

Abstract: BACKGROUND AND OBJECTIVES: Many adolescents with type 1 diabetes experience diabetes-related distress (DRD; the negative emotional reactions specific to managing diabetes), but most research on DRD among adolescents relies on cross-sectional data. We assess adolescents' longitudinal DRD patterns and predictors of chronic DRD. METHODS: This secondary analysis of data from a depression prevention clinical trial included 264 adolescents with type 1 diabetes randomly assigned to a resilience or education intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
0
39
0
1
Order By: Relevance
“…Many adolescents with T1DM experience diabetes-related distress, and this condition is often associated with suboptimal glycemic control, low levels of self-care, and reduced selfefficacy [12]. Previous studies of youths with T1DM have shown that chronic diabetes-related distress is associated with higher levels of depressive symptoms and higher HbA1c levels [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Many adolescents with T1DM experience diabetes-related distress, and this condition is often associated with suboptimal glycemic control, low levels of self-care, and reduced selfefficacy [12]. Previous studies of youths with T1DM have shown that chronic diabetes-related distress is associated with higher levels of depressive symptoms and higher HbA1c levels [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition to physical problems such as retinopathy, nephropathy, neuropathy and diabetic foot, 7 there are higher levels of emotional problems in individuals with type 2 diabetes which include depression, anxiety, aggression and emotional distress. 8,9 According to studies, about 20% to 40% of patients with type 2 diabetes experience emotional distress. 10,11 Emotional distress in individuals with type 2 diabetes is a worry and anxiety that is related to diabetes and exists from mild to severe level.…”
Section: Introductionmentioning
confidence: 99%
“…Another common challenge that adolescents face and that has been associated with suboptimal diabetes outcomes is diabetesrelated distress. 11 Diabetes distress refers to the fear of complications, fear of hypoglycemia, in addition to the range of stresses, strains and concerns that people who are diagnosed with diabetes have to live with on a daily basis. 12 Diabetes distress is not a proxy for clinical depression, but rather a reflection of an emotional response to a demanding health condition.…”
mentioning
confidence: 99%